miR-215 Modulates Ubiquitination to Impair Inflammasome Activation and Autophagy During Salmonella Typhimurium Infection in Porcine Intestinal Cells - Carmen Entrenas-García; José M. Suárez-Cárdenas; Raúl Fernández-Rodríguez; Rocío Bautista; M. Gonzalo Claros; Juan J. Garrido; Sara Zaldívar-López (Animals, 2025)
The host response to S. Typhimurium infection can be post-transcriptionally regulated by miRNAs. In this study, we investigated the role of miR-215 using both in vivo porcine infection models and in vitro intestinal epithelial cell lines. Several miRNAs were found to be dysregulated in the porcine ileum during infection with wild-type and SPI2-defective mutant strains of S. Typhimurium, with some changes being SPI2-dependent. Notably, miR-215 was significantly downregulated during infection. To explore its functional role, gain-of-function experiments were performed by transfecting porcine intestinal epithelial cells (IPEC-J2) with a miR-215-5p mimic, followed by label-free quantitative (LFQ) proteomic analysis. This analysis identified 157 proteins, of which 35 were downregulated in response to miR-215 overexpression, suggesting they are potential targets of this miRNA. Among these, E2 small ubiquitin-like modifier (SUMO)-conjugating enzyme UBC9 and E3 ubiquitin-ligase HUWE1 were identified as key targets, both of which are upregulated during S. Typhimurium infection. The miR-215-mediated downregulation of these proteins resulted in a significant decrease in overall ubiquitination, a process crucial for regulating inflammasome activation and autophagy. Consistently, inflammasome markers caspase 1 (CASP1) and apoptosis-associated speck-like protein containing a CARD (ASC), as well as autophagy markers microtubule-associated protein 1A/1B-light chain 3 (LC3B) and Ras-related protein Rab-11 (RAB11A), showed decreased expression in miR-215 mimic-transfected and infected IPEC-J2 cells. To further validate these findings, human intestinal epithelial cells (HT29) were used as a complementary model, providing additional insights into conserved immune pathways and extending the observations made in the porcine system. Overall, our findings demonstrate that miR-215 plays a significant role in modulating host inflammasome activation and autophagy by targeting proteins involved in ubiquitination during S. Typhimurium infection.